Globalization, foreign direct investment, and technology transfers : impacts on and prospects for developing countries - Kumar, Nagesh, 1958- (UNU/INTECH studies in new technology and development ;, 1998)
Summary: This book discusses emerging patterns of FDI and technology transfers, and the growth prospects for developing countries in the context of globalization.